A Time to Connect? On Tourism Policy Making in Iceland - Jóhannesson, Gunnar Þór (Stjórnsýslustofnun, 2012)
Tourism in Iceland has experienced a rapid growth during the last three decades and currently provides a substantial part of Iceland‘s foreign currency earnings. Tourism has often been described as a sector with huge potentialities on the island and after the banking crisis in 2008 tourism has been recognized as an important part of the national economy. This article explores efforts made by the central authorities to create a tourism policy. The main features in the history of tourism policy making are described but the focus remains on two phases, which cast light on its emergence and development. The article makes use of actor-network theory to highlight the heterogeneity and dynamics of tourism policy making. It is argued that tourism policy is an effect of complex set of relations and at times unexpected conjunctions and coincidences as well as being characterized by an apparent lack of relation between the authorities and the sector. In the two cases discussed the cod stock and volcanic ash particles play significant roles in shaping and accomplishing tourism policies. Ferðaþjónusta á Íslandi hefur vaxið mjög að umfangi síðustu þrjá áratugi og er nú svo komið að atvinnugreinin skaffar umtalsverðan hluta gjaldeyristekna þjóðarbúsins. Ferðaþjónustu hefur löngum verið lýst sem atvinnugrein með mikla framtíðarmöguleika og eftir bankahrunið 2008 hefur hún verið talin gegna mikilvægu hlutverki í endurreisn efnahagslífsins. Í þessari grein er fjallað um hvernig stjórnvöld hafa leitast við að móta stefnu í ferðaþjónustu. Megindráttum í sögu stefnumótunar í ferðaþjónustu er lýst og gripið sérstaklega niður í tvö tímabil sem varpa ljósi á tilurð hennar og mótun. Gerendanetskenningunni (Actor-network theory) er beitt til að draga fram margleitni og dýnamík í gerð stefnumótunar. Því er haldið fram að stefnumótun í ferðaþjónustu sé afurð flókinna tengsla og á tíðum óvæntra samtenginga og tilviljana auk þess að markast af meintu tengslaleysi stjórnvalda við atvinnugreinina. Í þeim tveim tilvikum sem lýst er leika ...